Social Capital of Women Leaders in the Indigenous Community of Osing, East Java, Indonesia: A Feminist Ethnography Research - Hannah, Neng (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2020)
Female leaders have been around since ancient Indonesia. However, fewer women become leaders than men. Female leadership is considered successful when it follows male standards. The purpose of this research is to reveal the experience of women's leadership in the Osing Banyuwangi indigenous community. This research employs qualitative research with a feminist ethnographic approach. The findings of this study show that there are three female village heads in the Osing indigenous community, namely Kemiren village, Rejosari village, and Kampunganyar village. All three women have the capital they need to be elected and lead the community. The capital they owned both in the quality and quantity of the relationship network they transform and are in the form of economic capital, cultural capital, and social capital. In conclusion, this social capital is owned by the female leader herself and is not an extension of the power of the other party. These capitals make them able to face challenges typically attributed to women's leadership namely negative stereotypes and double burdens.